Investigating TikTok Trends in Transcranial Direct Current Stimulation: A Comprehensive Descriptive Analysis - Silva‐Filho, Edson; Lima Alves da Silva, Tatiana Camila; Di‐Bonaventura, Silvia; Vieira, Letícia Amaro; Pegado, Rodrigo; Micussi, Maria Thereza Albuquerque Barbosa Cabral (The clinical teacher, 2025)
ABSTRACT Background Transcranial direct current stimulation (tDCS) has gained significant attention in both academic and clinical settings due to its potential benefits in treating various neurological conditions. However, the accessibility and accuracy of information on social media platforms, such as TikTok, can greatly influence public perception and understanding of this technology. Therefore, because the information on the platform is not peer‐reviewed, the analysis of the TikTok content is essential for the audience. Objective To assess the reliability, accuracy, quality of consumer health information and overall quality of the videos on TikTok pertaining to tDCS. Methods We conducted a search from 10 to 30 June 2024 using the terms ‘transcranial direct current stimulation’ and/or ‘tDCS’ to identify relevant videos on the TikTok platform. The videos were analysed based on the JAMA benchmark criteria, DISCERN, global quality score and the Patient Education Materials Assessment Tool. Results A total of 53 videos were included for analysis, with an average of approximately 40.000 views each. Most videos were uploaded by private users detailing their personal experiences. According to the JAMA benchmark, the majority of the videos lacked reliability and accuracy. The DISCERN assessment indicated that most videos were classified as very poor or poor. The global quality assessment revealed that the videos provided minimal useful information to the audience. However, the Patient Education Materials Assessment Tool results showed that most videos had moderate to high understandability but low actionability. Conclusion Most tDCS‐related videos on the TikTok platform exhibited low accuracy, reliability and overall quality. Additionally, the understandability and actionability for viewers were limited.